Silicon nitride-based multiphase ceramic with stable resistance and conduction characteristics and preparation method and application of silicon nitride-based multiphase ceramic

By adding TiCxN1-x phase to silicon nitride ceramics to form a conductive network, the problems of high resistivity and high temperature sensitivity of silicon nitride ceramics are solved, resistance stability and temperature stability are achieved, and its application in high-precision and tip components is broadened.

CN119591410APending Publication Date: 2025-03-11SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411643772.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Silicon nitride ceramics have problems of high resistivity and high temperature sensitivity in applications such as electrostatic suction cups, which limits its wide application in the electrical industry.

Method used

By adding a high-conductive TiCxN1-x phase with a positive temperature coefficient resistance characteristic to the silicon nitride ceramic, a conductive network is formed, which reduces the resistivity of the silicon nitride ceramic and neutralizes its resistance temperature sensitivity.

Benefits of technology

The resistance stability and temperature stability of silicon nitride ceramics have been achieved, and its application in high-precision components such as electrostatic suction cups, wafer heaters, infrared light sources has been broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591410A_ABST
    Figure CN119591410A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon nitride-based composite ceramic with stable resistance and conductive characteristics and a preparation method and application thereof. The silicon nitride composite ceramic comprises a Si3N4 main phase, a conductive second phase dispersed in the Si3N4 main phase and a sintering aid, according to the volume fraction of 100 vol%, the volume fraction of the Si3N4 main phase is 55-75 vol%, the volume fraction of the conductive second phase is 25-35 vol%, and the volume fraction of the sintering aid is 1-15 vol%; preferably, the volume fraction of the sintering aid is 5-10 vol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of inorganic non-metallic materials, and specifically relates to a silicon nitride-based composite ceramic with stable resistance and conductive properties, and a preparation method and application thereof. Background Art

[0002] At present, the manufacturing materials of electrostatic chucks are mainly aluminum oxide (Al2O3) and aluminum nitride (AlN) ceramics. Among them, Al2O3 ceramics have low thermal conductivity and poor mechanical properties, while AlN ceramics have good thermal conductivity and gradually become the mainstream material of electrostatic chucks, but the insufficient mechanical properties lead to the problem of poor reliability. Compared with the two, silicon nitride (Si3N4) ceramics have excellent properties such as high strength, high toughness, high thermal conductivity, and thermal shock resistance. Its theoretical thermal conductivity is 320W / m·K, and its bending strength can reach 800MPa. It is a more promising material for electrostatic chucks.

[0003] The adsorption force of the electrostatic chuck is inversely proportional to the resistivity of its dielectric layer, and the precision of semiconductor manufacturing requires the electrostatic chuck to have high resistance and stable electrical properties to ensure the yield and consistency of the product. However, Si3N4 ceramics are electrically insulating, with an intrinsic resistivity greater than 10 14 Ω·cm, the electrostatic adsorption function is weak; in addition, it is a negative temperature coefficient material, the resistivity decreases with increasing temperature, and the fluctuation is large. Studies have shown that a slight temperature fluctuation can cause a significant decrease in the resistivity of Si3N4 ceramics. In the invention patent "A silicon nitride composite ceramic material for insulating support and its preparation method 202410376318.3", its volume resistivity decreases by 28-42% only when the service temperature increases from room temperature to 80°C. Therefore, it is urgent to develop a silicon nitride-based composite ceramic with stable resistance and conductive properties in response to the service environment requirements of silicon nitride ceramics for electrostatic chucks. Summary of the invention

[0004] In response to the above problems, the present invention provides a silicon nitride-based composite ceramic with stable resistance and conductive properties, as well as a preparation method and application thereof, aiming to reduce the resistivity of silicon nitride ceramics and neutralize the temperature sensitivity of its electrical properties, and broaden the application of silicon nitride ceramics in high-precision components such as electrostatic chucks, wafer heaters, and infrared light sources.

[0005] In a first aspect, the present invention provides a silicon nitride-based composite ceramic having resistance-stable conductive properties, wherein the silicon nitride composite ceramic comprises: a Si3N4 main phase, a conductive second phase dispersed in the Si3N4 main phase, and a sintering aid; based on a volume fraction of 100 vol%, the volume fraction of the Si3N4 main phase is 55-75 vol%, the volume fraction of the conductive second phase is 25-35 vol%, and the volume fraction of the sintering aid is 1-15 vol%; preferably, the volume fraction of the sintering aid is 5-10 vol%.

[0006] Preferably, the conductive second phase is TiC x N 1-x , TiN, TiC, TiB2, TiO2, MoSi2, SiC, B4C; preferably, the conductive second phase is TiC x N 1-x , 0≤x≤1.

[0007] The inventors found during the research that Si3N4 is a negative temperature coefficient thermistor ceramic with a large bandgap (4-6 eV) that results in an extremely low free carrier concentration in the grains. The high potential barriers formed by defects and impurities at the grain boundaries also hinder electron transmission. Therefore, Si3N4 ceramics exhibit electrical insulation properties at room temperature, with a resistivity of more than 10 14 Ω·cm; With the increase of temperature, on the one hand, more electrons jump from the valence band to the conduction band, resulting in an increase in carrier concentration; on the other hand, the increase in temperature accelerates the thermal motion of electrons, resulting in an increase in mobility. These two reasons lead to a decrease in the resistivity of Si3N4 ceramics with increasing temperature. x N 1-x (0≤x≤1) has a positive temperature coefficient characteristic of metal-like resistance, and the resistivity is about 10 at room temperature. -5 Ω·cm, the temperature rises and enhances the phonon vibration, which leads to more obvious electron scattering, hindering the directional movement of electrons, and making its resistance increase with the increase of temperature. Therefore, the high conductive TiC with positive temperature coefficient resistance characteristics x N 1-x Adding it to highly insulating Si3N4 ceramics with negative temperature coefficient resistance characteristics can simultaneously achieve the purpose of reducing the resistivity of Si3N4 ceramics and neutralizing the resistance temperature sensitivity of the two, thereby realizing the controllable preparation of silicon nitride-based composite ceramics with stable resistance and conductive characteristics.

[0008] The Si3N4 in the silicon nitride-based composite ceramic with stable resistance and conductive properties is present in the β phase. x N 1-x It exists stably and is evenly dispersed in the β-Si3N4 matrix, forming a connected conductive network, which can effectively reduce the resistivity of Si3N4 ceramics and regulate the resistance sensitivity of Si3N4 ceramics.

[0009] Preferably, the sintering aid is a rare earth metal oxide and an alkaline earth metal oxide; the rare earth metal oxide is at least one of Y2O3, Yb2O3, La2O3, and Lu2O3; preferably Y2O3; the alkaline earth metal oxide is at least one of MgO, Al2O3, BaO, and CaO; preferably MgO; more preferably, the molar ratio of Y2O3 to MgO is 1:10 to 10:1; further preferably, it is 1:5 to 5:1.

[0010] Preferably, the density of the silicon nitride-based composite ceramic is 3.50-3.95 g·cm -3 ; The relative density of the silicon nitride-based composite ceramic is 95% to 100%; the resistance stability range of the silicon nitride-based composite ceramic is 15.5±2.4Ω·cm to 119.8±4.7Ω·cm; the resistance stability temperature range of the silicon nitride-based composite ceramic is from room temperature to 300 to 400°C.

[0011] In a second aspect, the present invention further provides a method for preparing the above-mentioned silicon nitride-based composite ceramic with stable resistance and conductive properties, comprising the following steps: (1) Si3N4 powder, TiC x N 1-x The powder, Y2O3 powder and MgO powder are mixed in proportion and ball-milled to obtain a ceramic slurry; (2) drying, crushing and sieving the obtained ceramic slurry to obtain ceramic powder; (3) The obtained ceramic powder is pressed into a shape and then sintered at a high temperature to obtain the silicon nitride-based composite ceramic.

[0012] Preferably, the Si3N4 powder is mainly α-Si3N4; the content of α-Si3N4 is ≥90wt%; preferably, the content of α-Si3N is ≥95wt%; The particle size of the Si3N4 powder is 0.1 to 1 μm, preferably 0.1 to 0.5 μm.

[0013] Preferably, the TiC x N 1-x The particle size of the powder is 0.5 to 3 μm, preferably 0.5 to 1 μm.

[0014] Preferably, the particle size of the Y2O3 powder is 50nm~5μm; the particle size of the MgO powder is 50nm~3μm.

[0015] Preferably, in step (1), the speed of the ball mill is 300 to 500 r / min. -1 ; The ball milling time is 4 to 24 hours.

[0016] Preferably, the solid content of the ceramic slurry is 40-60wt%; more preferably 45-55wt%.

[0017] Preferably, in step (2), the drying method is spray granulation or drying; the drying temperature is 70-120° C., and the time is 10-24 hours; and the sieving mesh size is 80-200 meshes.

[0018] Preferably, in step (3), the pressing method is dry pressing and / or isostatic pressing; preferably, the pressure of the dry pressing is 5 to 30 MPa; the pressure of the isostatic pressing is 150 to 250 MPa.

[0019] Preferably, in step (3), the high temperature sintering method is gas pressure sintering, hot pressing sintering, spark plasma sintering, hot isostatic pressing sintering or pressureless sintering; preferably hot pressing sintering; the parameters of the hot pressing sintering are: sintering temperature is 1700-1950°C; preferably 1750-1850°C; axial pressure is 15-50MPa; preferably 25-40MPa; holding time is 1-8h; preferably 1-4h; heating rate from room temperature to 1000°C is 5-20°C·min -1 ; Heating rate from 1000 to 1950°C is 2 to 10°C min -1 ; In order to inhibit the decomposition of Si3N4, the sintering atmosphere is nitrogen and the gas pressure is 0.1~1MPa.

[0020] Preferably, the preparation method further comprises: after the high temperature sintering is completed, -1 The temperature is controlled to cool to 800-1000℃ and then cooled to room temperature with the furnace.

[0021] In a third aspect, the present invention also provides the application of the above-mentioned silicon nitride-based composite ceramics with stable resistance and conductive properties in high-precision component materials, and the high-precision component materials include electrostatic chucks, wafer heaters, infrared light sources, and precision instruments.

[0022] Beneficial effects: (1) In the prior art, silicon nitride ceramics exhibit electrical insulation properties, with a resistivity exceeding 10 14 Ω·cm, and there is a high temperature drift phenomenon, which limits its application in the electrical industry. The present invention uses high-conductivity TiC with positive temperature coefficient resistance characteristics x N 1-x (0≤x≤1) is added to the high-insulation Si3N4 ceramic with negative temperature coefficient resistance characteristics, thereby achieving the purpose of reducing the resistivity of Si3N4 ceramics and neutralizing the temperature sensitivity of the resistance of the two, and realizing the controllable preparation of silicon nitride-based composite ceramics with stable resistance and conductive characteristics; (2) The resistance stability range of the silicon nitride-based composite ceramics prepared by the present invention is 15.5±2.4Ω·cm~119.8±4.7Ω·cm, and the resistance stability temperature range is from room temperature to 300~400℃. Based on the basic performance advantages of silicon nitride ceramics such as high strength, high wear resistance, and high chemical stability, the silicon nitride-based composite ceramics with stable resistance and conductive properties prepared by the present invention are expected to be used in high-precision components such as electrostatic chucks, wafer heaters, and infrared light sources, which broadens the application field of silicon nitride ceramics and has extremely high industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Containing different contents of TiC 0.5 N 0.5 SEM image of the polished surface of silicon nitride-based composite ceramics (cracks are caused by indentation testing); Figure 2 Containing different contents of TiC 0.5 N 0.5 Resistivity change curve of silicon nitride-based composite ceramics at different test temperatures. DETAILED DESCRIPTION

[0024] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0025] In the present invention, a highly conductive TiC having a positive temperature coefficient resistance characteristic is added to a highly insulating Si3N4 ceramic matrix having a negative temperature coefficient resistance characteristic. x N 1-x (0≤x≤1) phase, achieving the purpose of reducing the resistivity of Si3N4 ceramics and neutralizing the resistance-temperature sensitivity of the two, and obtaining silicon nitride-based composite ceramics with stable resistance and conductive properties, which is expected to be used in high-precision components such as electrostatic chucks, wafer heaters, infrared light sources, etc., and has extremely high industrial value.

[0026] The following is an exemplary description of the method for preparing the silicon nitride composite ceramic with stable resistance and conductive properties provided by the present invention.

[0027] Preparation of ceramic slurry. According to the formula of silicon nitride composite ceramics with stable resistance and conductive properties, Si3N4 powder, conductive second phase powder and sintering aid are weighed, the above raw materials are mixed into anhydrous ethanol, silicon nitride balls are added as ball milling media, and ceramic slurry is obtained by ball milling.

[0028] In an optional embodiment, based on a volume fraction of 100 vol%, the volume fraction of Si3N4 powder is 55-75 vol%, the volume fraction of the conductive second phase powder is 25-35 vol%, and the volume fraction of the sintering aid is 1-15 vol%; wherein the volume fraction of the sintering aid is preferably 5-10 vol%. Wherein, if the amount of sintering aid added is too little, a sufficient amount of liquid phase cannot be formed, resulting in difficulty in densification of the sample; if the amount of sintering aid added is too much, the grain boundary phase content is increased, which will hinder electronic conduction and affect the conductivity of the sample. If the amount of conductive second phase added is too much, the composite ceramic tends to exhibit metal-like electrical properties, and the resistivity increases with increasing temperature; if the amount of conductive second phase added is too little, it is difficult to neutralize the temperature sensitivity of silicon nitride ceramics, and even it is impossible to form a conductive network in the silicon nitride ceramic matrix.

[0029] In an optional embodiment, the conductive second phase powder is TiC x N 1-x , TiN, TiC, TiB2, TiO2, MoSi2, SiC, B4C; preferably, the conductive second phase powder is TiC x N 1-x Powder, 0≤x≤1.

[0030] In an optional embodiment, the sintering aid is a rare earth metal oxide and an alkaline earth metal oxide; the rare earth metal oxide is at least one of Y2O3, Yb2O3, La2O3, and Lu2O3; preferably Y2O3; the alkaline earth metal oxide is at least one of MgO, Al2O3, BaO, and CaO; preferably MgO; more preferably, the molar ratio of Y2O3 to MgO is 1:10 to 10:1; preferably 1:5 to 5:1.

[0031] In an optional embodiment, the solid content of the ceramic slurry is 40-60 wt %; preferably, the solid content of the ceramic slurry is 45-55 wt %.

[0032] As an example of ceramic slurry preparation (with TiC as the conductive second phase x N 1-x Powder, sintering aid is Y2O3 powder and MgO powder for example), including: Si3N4 powder, TiC x N 1-x The powder, Y2O3 powder and MgO powder are mixed and prepared into a mixed slurry with anhydrous ethanol as solvent, and the solid content is controlled to be 40-60wt%, preferably 45-55wt%. The planetary ball milling method is adopted, and the silicon nitride ceramic ball is used as the ball milling mixing medium, and the ball milling speed is controlled to be 300-500r·min -1 , the ball milling time is 4 to 24 hours to ensure that all raw materials are evenly dispersed.

[0033] Preparation of ceramic powder: The ceramic slurry is dried, crushed and sieved to obtain ceramic powder.

[0034] In an optional embodiment, the drying method is spray granulation or drying; the drying temperature is 70-120°C and the time is 10-24 hours. The mesh size of the sieve is 80-200 mesh. The sieve granulation forms a uniform ceramic powder, which is conducive to sintering densification.

[0035] Ceramic green body molding: Ceramic powder is pressed into shape to obtain a ceramic green body.

[0036] In an optional embodiment, the pressing method is dry pressing and / or isostatic pressing; preferably, the pressure of the dry pressing is 5 to 30 MPa; the pressure of the isostatic pressing is 150 to 250 MPa.

[0037] Ceramic high temperature sintering. The ceramic blank is placed in a graphite mold and sintered at high temperature to obtain a silicon nitride composite ceramic with stable resistance and conductive properties.

[0038] In an optional embodiment, the high temperature sintering method is gas pressure sintering, hot pressing sintering, spark plasma sintering, hot isostatic pressing sintering or pressureless sintering; preferably hot pressing sintering; the parameters of the hot pressing sintering are: sintering temperature is 1700-1950°C; preferably 1750-1850°C; axial pressure is 15-50MPa; preferably 25-40MPa; holding time is 1-8h; preferably 1-4h; heating rate from room temperature to 1000°C is 5-20°C·min -1 ; Heating rate from 1000 to 1950°C is 2 to 10°C min -1 ; To inhibit the decomposition of Si3N4, the sintering atmosphere is nitrogen, and the gas pressure is 0.1MPa~1MPa. After the high-temperature sintering is completed, the temperature is ≤15℃·min -1 The temperature is controlled to cool to 800-1000℃ and then cooled to room temperature with the furnace.

[0039] In the present invention, the Archimedes displacement method is used to measure the bulk density of the sample, and the relative density of the sample is calculated based on the law of mixtures.

[0040] In the present invention, the obtained silicon nitride-based composite ceramic is ground on both sides to form a disc with a thickness of 1 mm and a diameter of 15 mm, and silver paste electrodes are evenly coated on both sides, and placed in a muffle furnace at 600°C for 15 minutes to obtain a silver electrode. The resistivity of the sample is measured at a test temperature range of room temperature to 400°C, and a heating rate of 5°C·min -1 .

[0041] The density of the silicon nitride-based composite ceramic prepared by the present invention is 3.50-3.95 g·cm -3 The relative density is 95% to 100%, the resistance stability range of silicon nitride-based composite ceramics is 15.5±2.4Ω·cm to 119.8±4.7Ω·cm, and the resistance stability temperature range is from room temperature to 300 to 400°C.

[0042] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0043] Example 1 α-Si3N4 powder, TiC 0.5 N 0.5 Powder, Y2O3 powder and MgO powder are used as raw materials. According to the calculation of complete density, the volume proportion of Si3N4 phase in the sintered composite ceramic is 64vol%, TiC 0.5 N 0.5 The phase volume accounts for 30 vol%, the sum of the volume of Y2O3 and MgO sintering aid accounts for 6 vol%, and the molar ratio of Y2O3 to MgO is 1:3. The raw materials are weighed according to the total amount of 100g, and an appropriate amount of anhydrous ethanol is added to adjust the solid content to 45wt%. 200g of silicon nitride balls are added as ball milling media, and a planetary ball mill is used at 400r·min -1 The ceramic slurry was obtained by ball milling at a speed of 12 hours to ensure that all raw materials were evenly dispersed. The obtained ceramic slurry was dried at 80°C for 12 hours, crushed and passed through a 100-mesh sieve to obtain ceramic powder. The obtained ceramic powder was dry-pressed under an axial pressure of 20MPa and then loaded into a graphite mold. Silicon nitride-based composite ceramics were obtained by hot pressing, wherein the axial pressure was 30MPa, the sintering temperature was 1800°C, the holding time was 2h, and the heating rate from room temperature to 1000°C was 10°C·min -1 , the heating rate from 1000 to 1800°C is 5°C·min -1 The sintering atmosphere is nitrogen and the pressure is 0.1MPa. After the high temperature sintering is completed, the temperature is 10℃·min -1 The sample was cooled to 800°C at a cooling rate and then cooled to room temperature along with the furnace.

[0044] The SEM image of the polished surface of the silicon nitride-based composite ceramic prepared in Example 1 is as follows: Figure 1 As shown in the figure, the sample is basically dense, TiC0.5 N 0.5 The grains form a conductive network. The density of the sintered silicon nitride-based composite ceramics was measured by the Archimedes method to be 3.77 g cm -3 , the relative density calculated based on the mixture law is 97.86%. The obtained silicon nitride-based composite ceramic was ground on both sides and processed into a disc with a thickness of 1 mm and a diameter of 15 mm. Silver paste electrodes were evenly coated on both sides and placed in a muffle furnace at 600°C for 15 minutes to obtain a silver electrode. After testing, the sample has good conductivity in the range of room temperature to 400°C, and the resistivity is stable at 15.5±2.4Ω·cm( Figure 2 ), the fluctuation is extremely small, and it is expected to be used as a resistance-stable conductive material.

[0045] Example 2 α-Si3N4 powder, TiC 0.5 N 0.5 Powder, Y2O3 powder and MgO powder are used as raw materials. According to the calculation of complete density, the volume proportion of Si3N4 phase in the sintered composite ceramic is 69vol%, TiC 0.5 N 0.5 The phase volume ratio is 25 vol%, the volume ratio of Y2O3 and MgO sintering aids is 6 vol%, and the molar ratio of Y2O3 to MgO is 1:3. The raw materials are weighed according to the total amount of 100g, and an appropriate amount of anhydrous ethanol is added to adjust the solid content to 45wt%. 200g of silicon nitride balls are added as ball milling media, and a planetary ball mill is used at 400r·min -1 The ceramic slurry was obtained by ball milling at a speed of 12 hours to ensure that all raw materials were evenly dispersed. The obtained ceramic slurry was dried at 80°C for 12 hours, crushed and passed through a 100-mesh sieve to obtain ceramic powder. The obtained ceramic powder was dry-pressed under an axial pressure of 20MPa and then loaded into a graphite mold. Silicon nitride-based composite ceramics were obtained by hot pressing, wherein the axial pressure was 30MPa, the sintering temperature was 1800°C, the holding time was 2h, and the heating rate from room temperature to 1000°C was 10°C·min -1 , the heating rate from 1000 to 1800°C is 5°C·min -1 The sintering atmosphere is nitrogen and the pressure is 0.1MPa. After the high temperature sintering is completed, the temperature is 10℃·min -1 The sample was cooled to 800°C at a cooling rate and then cooled to room temperature along with the furnace.

[0046] The SEM image of the polished surface of the silicon nitride-based composite ceramic prepared in Example 2 is as follows: Figure 1 As shown in the figure, the sample is basically dense, TiC 0.5 N 0.5 The grains form a conductive network. The density of the sintered silicon nitride-based composite ceramics was measured by the Archimedes method to be 3.68 g cm-3 , the relative density calculated based on the mixture law is 97.99%. The obtained silicon nitride-based composite ceramics were ground on both sides and processed into discs with a thickness of 1 mm and a diameter of 15 mm. Silver paste electrodes were evenly coated on both sides and placed in a muffle furnace at 600°C for 15 minutes to obtain silver electrodes. After testing, the sample has good conductivity in the range of room temperature to 400°C, and has good resistance stability in the range of room temperature to 300°C, with a resistivity stable at 119.8±4.7Ω·cm( Figure 2 ), the fluctuation is extremely small, and it is expected to be used as a resistance-stable conductive material.

[0047] Comparative Example 1 α-Si3N4 powder, TiC 0.5 N 0.5 Powder, Y2O3 powder and MgO powder are used as raw materials. According to the calculation of complete density, the volume proportion of Si3N4 phase in the sintered composite ceramic is 74vol%, TiC 0.5 N 0.5 The phase volume accounts for 20 vol%, the volume and proportion of Y2O3 and MgO sintering aids are 6 vol%, and the molar ratio of Y2O3 to MgO is 1:3. The raw materials are weighed according to the total amount of 100g, and an appropriate amount of anhydrous ethanol is added to adjust the solid content to 45wt%. 200g of silicon nitride balls are added as ball milling media, and a planetary ball mill is used at 400r·min -1 The ceramic slurry was obtained by ball milling at a speed of 12 hours to ensure that all raw materials were evenly dispersed. The obtained ceramic slurry was dried at 80°C for 12 hours, crushed and passed through a 100-mesh sieve to obtain ceramic powder. The obtained ceramic powder was dry-pressed under an axial pressure of 20MPa and then loaded into a graphite mold. Silicon nitride-based composite ceramics were obtained by hot pressing, wherein the axial pressure was 30MPa, the sintering temperature was 1800°C, the holding time was 2h, and the heating rate from room temperature to 1000°C was 10°C·min -1 , the heating rate from 1000 to 1800°C is 5°C·min -1 The sintering atmosphere is nitrogen and the pressure is 0.1MPa. After the high temperature sintering is completed, the temperature is 10℃·min -1 The sample was cooled to 800°C at a cooling rate and then cooled to room temperature along with the furnace.

[0048] The SEM image of the polished surface of the silicon nitride-based composite ceramic prepared in this comparative example 1 is as follows Figure 1 As shown in the figure, the sample is basically dense, but TiC 0.5 N 0.5 The grain distribution continuity is poor. The density of the sintered silicon nitride-based composite ceramics was measured by the Archimedes method to be 3.58 g·cm -3, the relative density calculated based on the mixture law is 97.89%. The obtained silicon nitride-based composite ceramic was ground on both sides and processed into a disc with a thickness of 1 mm and a diameter of 15 mm. Silver paste electrodes were evenly coated on both sides and placed in a muffle furnace at 600°C for 15 minutes to obtain a silver electrode. After testing, the resistivity of the measured sample decreased significantly with increasing temperature in the range of room temperature to 400°C, specifically from 793.6Ω·cm to 142.7Ω·cm ( Figure 2 ). This is because the amount of conductive second phase added is too small to neutralize the temperature sensitivity of silicon nitride ceramics, and the composite ceramics still show the typical characteristics of silicon nitride ceramics that the resistivity changes with temperature.

[0049] Comparative Example 2 Using α-Si3N4 powder, Y2O3 powder and MgO powder as raw materials, according to the calculation of complete density, the volume proportion of Si3N4 phase in the sintered composite ceramic is controlled to be 94vol%, the volume and proportion of Y2O3 and MgO sintering aids are 6vol%, and the molar ratio of Y2O3 to MgO is 1:3. The raw materials are weighed according to the total amount of 100g, and an appropriate amount of anhydrous ethanol is added to adjust the solid content to 45wt%, and 200g of silicon nitride balls are added as ball milling media. A planetary ball mill is used at 400r·min -1 The ceramic slurry was obtained by ball milling at a speed of 12 hours to ensure that all raw materials were evenly dispersed. The obtained ceramic slurry was dried at 80°C for 12 hours, crushed and passed through a 100-mesh sieve to obtain ceramic powder. The obtained ceramic powder was dry-pressed under an axial pressure of 20MPa and then loaded into a graphite mold. Silicon nitride-based composite ceramics were obtained by hot pressing, wherein the axial pressure was 30MPa, the sintering temperature was 1800°C, the holding time was 2h, and the heating rate from room temperature to 1000°C was 10°C·min -1 , the heating rate from 1000 to 1800°C is 5°C·min -1 The sintering atmosphere is nitrogen and the pressure is 0.1MPa. After the high temperature sintering is completed, the temperature is 10℃·min -1 The sample was cooled to 800°C at a cooling rate and then cooled to room temperature along with the furnace.

[0050] The SEM image of the polished surface of the silicon nitride-based composite ceramic prepared in this comparative example 2 is as follows Figure 1 As shown in the figure, the sample is basically dense. The density of the sintered silicon nitride-based composite ceramics was 3.20 g cm -3 The relative density is 97.81% calculated based on the mixture law. The silicon nitride-based composite ceramic was ground on both sides and processed into a disc with a thickness of 1 mm and a diameter of 15 mm. Silver paste electrodes were coated on both sides and placed in a muffle furnace at 600°C for 15 minutes to obtain a silver electrode. The test showed that the resistivity of the sample decreased significantly with increasing temperature in the range of room temperature to 400°C, from 1013 The Ω·cm level decreased by 3 orders of magnitude to 10 10 The resistivity of silicon nitride ceramics varies with temperature.

Claims

1. A silicon nitride-based composite ceramic with stable resistance and conductive properties, characterized in that: The silicon nitride composite ceramic includes: a Si3N4 main phase, a conductive second phase dispersed in the Si3N4 main phase and a sintering aid; based on a volume fraction of 100 vol%, the volume fraction of the Si3N4 main phase is 55-75 vol%, the volume fraction of the conductive second phase is 25-35 vol%, and the volume fraction of the sintering aid is 1-15 vol%; preferably, the volume fraction of the sintering aid is 5-10 vol%.

2. The silicon nitride-based composite ceramic with stable resistance and conductive properties according to claim 1, characterized in that: The conductive second phase is TiC x N 1-x , TiN, TiC, TiB2, TiO2, MoSi2, SiC, B4C; preferably, the conductive second phase is TiC x N 1-x , 0≤x≤1.

3. The silicon nitride-based composite ceramic with stable resistance and conductive properties according to claim 1 or 2, characterized in that: The sintering aid is a rare earth metal oxide and an alkaline earth metal oxide; the rare earth metal oxide is at least one of Y2O3, Yb2O3, La2O3, and Lu2O3; preferably Y2O3; the alkaline earth metal oxide is at least one of MgO, Al2O3, BaO, and CaO; preferably MgO; more preferably, the molar ratio of Y2O3 to MgO is 1:10 to 10:1; further preferably 1:5 to 5:

1.

4. The silicon nitride-based composite ceramic with stable resistance and conductive properties according to any one of claims 1 to 3, characterized in that: The density of the silicon nitride-based composite ceramic is 3.50 to 3.95 g·cm -3 ; The relative density of the silicon nitride-based composite ceramic is 95% to 100%; the resistance stability range of the silicon nitride-based composite ceramic is 15.5±2.4Ω·cm to 119.8±4.7Ω·cm; the resistance stability temperature range of the silicon nitride-based composite ceramic is from room temperature to 300 to 400°C.

5. A method for preparing a silicon nitride-based composite ceramic having resistance-stable conductive properties according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Si3N4 powder, TiC x N 1-x The powder, Y2O3 powder and MgO powder are mixed in proportion and ball-milled to obtain a ceramic slurry; (2) drying, crushing and sieving the obtained ceramic slurry to obtain ceramic powder; (3) The obtained ceramic powder is pressed into a shape and then sintered at a high temperature to obtain the silicon nitride-based composite ceramic.

6. The preparation method according to claim 5, characterized in that: The Si3N4 powder is mainly α-Si3N4; the content of α-Si3N is ≥90wt%; preferably, the content of α-Si3N is ≥95wt%; The particle size of the Si3N4 powder is 0.1 to 1 μm, preferably 0.1 to 0.5 μm.

7. The preparation method according to claim 5 or 6, characterized in that: The TiC x N 1-x The particle size of the powder is 0.5 to 3 μm, preferably 0.5 to 1 μm; The particle size of the Y2O3 powder is 50nm to 5μm; The particle size of the MgO powder is 50nm-3μm.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (1), the rotation speed of the ball mill is 300 to 500 r / min. -1 ; The ball milling time is 4 to 24 hours; The solid content of the ceramic slurry is 40-60 wt %, preferably 45-55 wt %.

9. The preparation method according to any one of claims 5 to 8, characterized in that: In step (2), the drying method is spray granulation or drying; the drying temperature is 70 to 120° C. and the drying time is 10 to 24 hours; The mesh number of the sieving is 80 to 200 meshes.

10. The preparation method according to any one of claims 5 to 9, characterized in that: In step (3), the pressing method is dry pressing or / and isostatic pressing; preferably, the pressure of the dry pressing is 5 to 30 MPa; the pressure of the isostatic pressing is 150 to 250 MPa; The high temperature sintering method is gas pressure sintering, hot pressing sintering, spark plasma sintering, hot isostatic pressing sintering or pressureless sintering; preferably hot pressing sintering; the parameters of the hot pressing sintering are: sintering temperature is 1700-1950°C; preferably 1750-1850°C; axial pressure is 15-50MPa; preferably 25-40MPa; holding time is 1-8h; preferably 1-4h; heating rate from room temperature to 1000°C is 5-20°C·min -1 ; Heating rate from 1000 to 1950°C is 2 to 10°C min -1 ; The sintering atmosphere is nitrogen, and the gas pressure is 0.1~1MPa.

11. The preparation method according to any one of claims 5 to 10, characterized in that: The preparation method further comprises: after the high temperature sintering is completed, -1 The temperature is controlled to cool to 800-1000℃ and then cooled to room temperature with the furnace.

12. Application of silicon nitride-based composite ceramics with stable resistance and conductive properties according to any one of claims 1 to 4 in high-precision component materials, characterized in that: The high-precision and advanced component materials include electrostatic chucks, wafer heaters, infrared light sources, and precision instruments.

Citation Information

Patent Citations

  • Silicon nitride multiphase ceramic material for insulating support and preparation method of silicon nitride multiphase ceramic material

    CN118271098A